Incidence of abnormal termination of pregnancies in dairy cattle - SINGH, BALVIR; KUMAR, D (The Indian Journal of Animal Reproduction, 2007)
Data on 3484 calving records of 811 cows (Jersey, crossbred and Hariana) were analysed for estimating the effect of genetic and non-genetic factors on abnormal termination of pregnancies. The overall incidence of abortion, stillbirth, premature birth and total abnormal calving was I. 70, 1.06, 0.85 and 3.6 I % in pluriparous Jersey cows. The corresponding figures were 4.21, 1.49, 0.93 and 6.64 % in crossbred and 2.31, 0.88, 0.34 and 3.53 % in Hariana pluriparous cows. Farm and season of calving had significant effect on abnormal calving in all the genetic groups of pluriparous cows. Incidence of abortion was significantly influenced by farm in Hariana and by both farm and season in crossbred cattle. However, occurrence of stillbirth and premature birth was not affected by farm, period, season and parity in all the genetic groups except still birth in crossbred pluriparous cows. Genetic groups had significant effect on abortions and total abnormal calving. Crossbred pluriparous cows had significantly higher incidence of abortions and abnormal calving than purebreds. Maximum overall abnormal termination of pregnancy was recorded during 8th month of pregnancy and average gestation period for overall termination of pregnancies was 231.1± 16.8, 216.4±14.3 and 219.2±12.7 days in Jersey, crossbred and Hariana cows, respectively. Heritability and repeatability estimates of all the traits were low to very low in all the genetic groups.